A journey of a Filipino pre-service teacher before entering the Department of Education - Donnabel B. Bihasa; Helen B. Madrigal; Elizabeth M. Ladia (Eureka: Journal of Educational Research, 2024)
The journey of pre-service teachers in the Philippines was a transformative and crucial phase that involved comprehensive preparation, training, and personal growth. This research explored the experiences and challenges encountered by Filipino pre-service teachers and the factors that influenced the duration of their journey before they officially entered the Department of Education (DepEd). The research utilized a mixed-method design. The participants were sixty (60) pre-service teachers from different Teacher Education Institutions across the Philippines. Results showed that the duration of entering DepEd varied for each pre-service teacher based on different factors and their unique circumstances. Additionally, changes in policies, educational reforms, or external factors influenced the timeline for entering the department. The timeline for pre-service teachers to secure employment within the education department ranged from several months to a year or more, depending on the combination of academic requirements, licensure examinations, and bureaucratic processes they needed to complete. The duration of the transition process varied based on individual circumstances, such as qualifications, networking efforts, flexibility, and the specific conditions of the job market and educational institutions in a particular region. These findings implied that educational institutions, policymakers, and stakeholders could make informed decisions and implement targeted reforms that expedited the employment process for pre-service teachers. It was important to strike a balance between efficiency and maintaining high educational standards, ensuring that the reforms contributed to the overall quality of the education system.